Penerapan Peramalan Penjualan Sembako Menggunakan Metode Single Moving Average - Nia Kurnia (Jurnal Ilmiah Wahana Pendidikan, 2022)
The problem that is often faced by shop owners is that they cannot predict the stock of goods to be purchased, this is not only required by reliability and instinct.grocery store for retail the period January 2021 to July in 2022. The problem with the Dedeh retail is that it cannot predict the stock of basic necessities. data processing historical using the SMA (Single Moving Average) prediction in movement 2, calculating error from the prediction results using the MAD (Mean Absolute Deviation), MSE (Mean Square Error) and MAPE (mean absolute percentage error) methods. The final results were obtained after going through the process of calculating predictions and calculating errorsgrocery store retail that had a high level of accuracy were movement 8 in rice with an accuracy rate of 83.91%, MAD 33.33, MAPE 16.09%, and MSE 1666.67 with forecasting results of 475 (Kg) for predicting accuracy in July 2022. So the SMA method can provide a solution for predicting the stock of goods selling groceries, retail so that the stock of these items can be adjusted.